An Investigation of EFL Classroom Interaction by Using Flanders Interaction Analysis Category System (FIACS) - Ari Ayunda; Endang Komariah; Diana Achmad (Research in English and Education Journal, 2021)
Flanders Interaction Analysis Category System (FIACS) is a three-category system of communication possibilities inside the classroom. The aim of this study is to find out the percentage of teacher talk, direct and indirect, and students talk for second grade high school student. This study was conducted at SMA Labrotarium Unsyiah Banda Aceh. An English teacher from SMA Labroratorium Unsyiah was selected as the subject of this study while the object of this study was the teacher talk and the students talk during the classroom interaction in the teaching and learning process inside the classroom. The method of this study was qualitative study. The writer used observation sheet and video recording as instruments of this study. The result of this study showed that the percentage of indirect teacher talk category was 9.7%, direct teacher talk category was 40,32%, and the percentage of students’ talk was 50% for the first meeting. However, there was a different percentage for the second meeting. More than 50% of verbal behavior inside the classroom for the second meeting was spent by students’ talk category, followed by direct teacher talk category, 32,21%, and indirect teacher talk category, 16.8%. There was a little improvement between the first meeting and the second meeting in the category of students talk category and indirect teacher talk category.